2007
DOI: 10.1093/hmg/ddm367
|View full text |Cite
|
Sign up to set email alerts
|

Selective vulnerability of motor neurons and dissociation of pre- and post-synaptic pathology at the neuromuscular junction in mouse models of spinal muscular atrophy

Abstract: Proximal spinal muscular atrophy (SMA) is a common autosomal recessive childhood form of motor neuron disease. Previous studies have highlighted nerve- and muscle-specific events in SMA, including atrophy of muscle fibres and post-synaptic motor endplates, loss of lower motor neuron cell bodies and denervation of neuromuscular junctions caused by loss of pre-synaptic inputs. Here we have undertaken a detailed morphological investigation of neuromuscular synaptic pathology in the Smn-/-;SMN2 and Smn-/-;SMN2;Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
376
4
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(421 citation statements)
references
References 37 publications
37
376
4
2
Order By: Relevance
“…S3), indicating that the SMA mice are capable of expressing Z + agrin. However, the skipping of Z exons and the resulting Z + agrin protein deficiency in SMA MNs between P1 and P3 would impair postsynaptic AChR clustering, as observed at P5 in this SMA model (7)(8)(9).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…S3), indicating that the SMA mice are capable of expressing Z + agrin. However, the skipping of Z exons and the resulting Z + agrin protein deficiency in SMA MNs between P1 and P3 would impair postsynaptic AChR clustering, as observed at P5 in this SMA model (7)(8)(9).…”
Section: Discussionmentioning
confidence: 73%
“…Major morphological and biochemical deficits have been found at neuromuscular junctions (NMJs) and sensory-motor synapses. NMJ defects are first detectable at postnatal day 5 (P5), including presynaptic defects of terminal arborization and intermediate neurofilament aggregation in MNs, poor postsynaptic organization of AChRs in muscle, as well as reduced synaptic vesicle density and release at the NMJ (7)(8)(9). Importantly, similar NMJ defects have been reported in type I (the most severe type) SMA human fetuses (10).…”
mentioning
confidence: 85%
“…49 We examined TVA preparations of SMA and control littermates at P0, P5 and P8 to assess when NMJ defects become apparent. NMJ endplate size of the TVA began to lag behind at P5 in SMA as compared with control animals (Figures 5a, c and d).…”
Section: Jnj-26481585 Shows Upregulation Of Smn Protein Levels In Vivomentioning
confidence: 99%
“…However, how suboptimal levels of SMN lead to SMA is largely unknown. Multiple studies in SMA mouse models revealed widespread synaptic defects in neuromuscular junctions (NMJs), including neurofilament accumulation, poor terminal arborization, immature endplates, reduced quantal content, disturbed calcium homeostasis, and decreased remodeling potential; these defects precede motor neuron death (Cifuentes-Diaz et al 2002;Le et al 2005;Jablonka et al 2007;Kariya et al 2008;Murray et al 2008Murray et al , 2012Kong et al 2009;Ling et al 2010;Ruiz et al 2010;Lee et al 2011), suggesting that the NMJ alterations are the initial consequence of SMN deficiency, Ó 2015 Hua et al This article is distributed exclusively by Cold Spring Harbor Laboratory Press for the first six months after the full-issue publication date (see http://genesdev.cshlp.org/site/misc/terms.xhtml). After six months, it is available under a Creative Commons License (Attribution-NonCommercial 4.0 International), as described at http:// creativecommons.org/licenses/by-nc/4.0/.…”
mentioning
confidence: 99%